Mantle superplumes induce geomagnetic superchrons - Olson, Peter; Amit, Hagay (Frontiers in Earth Science, 2015)
We use polarity reversal systematics from numerical dynamos to quantify the hypothesis that the modulation of geomagnetic reversal frequency, including geomagnetic superchrons, results from changes in core heat flux related to growth and collapse of lower mantle superplumes. We parameterize the reversal frequency sensitivity from numerical dynamos in terms of average core heat flux normalized by the difference between the present-day core heat flux and the core heat flux at geomagnetic superchron onset. A low-order polynomial fit to the 0-300 Ma Geomagnetic Polarity Time Scale (GPTS) reveals that a decrease in core heat flux relative to present-day of approximately 30% can account for the Cretaceous Normal Polarity and Kiaman Reverse Polarity Superchrons, whereas the hyper-reversing periods in the Jurassic require a core heat flux equal to or higher than present-day. Possible links between GPTS transitions, large igneous provinces (LIPs), and the two lower mantle superplumes are explored. Lower mantle superplume growth and collapse induce GPTS transitions by increasing and decreasing core heat flux, respectively. Age clusters of major LIPs postdate transitions from hyper-reversing to superchron geodynamo states by 30-60 Myr, suggesting that superchron onset may be contemporaneous with LIP-forming instabilities produced during collapses of lower mantle superplumes.